From Rags to Comfort: Women Holocaust Survivors Rebuilding Lives in Montreal, 1947-1958 - Abramson, Zelda (Canadian Jewish Studies / Études juives canadiennes, 2015)
The majority of holocaust survivors who came to Canada settled in Montreal. Most came with little if any money or material goods. Within a relatively short period of time the immigrant survivors transitioned from poor-new immigrant to successful or at least comfortable Canadian. The benchmarks for family economic success are often rooted in man’s work and income. Drawing on in-depth interviews with survivors who arrived in Montreal between 1948 and 1958, and Jewish Immigrant Aid case files, I argue research that pays attention to the dailiness of women survivors’ lives offers a more nuanced understanding of their success narrative. La majorité des survivants de la Shoah ayant immigré au Canada se sont installés à Montréal, la plupart avec très peu d’argent et de biens matériels. Relativement rapidement, ils ont amélioré leurs conditions de vie bénéficiant d’un niveau de vie élevé ou tout au moins confortable. Le succès économique d’une famille est souvent mesuré à l’aune du salaire et du travail de l’homme. En se basant sur des entretiens approfondis avec des survivant-e-s qui sont arrivé-e-s à Montréal entre 1948 et 1958, et sur des dossiers individuels d’organisations juives d’aide à l’immigration, cette recherche met en lumière la vie quotidienne des femmes survivantes et permet de nuancer le récit classique de leur réussite.